Functionality of Community Managed DWSS: A Case Study of Water Supply Schemes in Simta Rural Municipality, Surkhet, Nepal - Adhikari, Raju; Dahal, Khetraj; Dhakal, Sujeet (International Journal on Engineering Technology, 2026)
Community-managed drinking water supply systems (DWSS) constitute the backbone of rural water service delivery in Nepal. Despite substantial investments and high nominal coverage, the long-term functionality of these systems remains a persistent challenge. This study assesses the functionality status of community-managed DWSS and identifies key factors influencing their performance in Simta RM of Surkhet District, Nepal. A mixed-methods approach was adopted, combining a quantitative scheme-level survey of ten water supply schemes with focus group discussions, key informant interactions, and field observations. Functionality was evaluated using nationally recognized indicators encompassing technical, environmental, institutional, and financial dimensions, while influencing factors were ranked using a RII based on Likert-scale responses. The results indicate that 70% of the surveyed schemes were at no or low risk of functionality failure, 20% were at some risk, and 10% were at high risk. Institutional and financial factors—particularly the activeness of UCs, availability of O&M funds, and presence of trained VMWs—were found to exert the strongest influence on functionality, followed by technical and environmental factors. The findings highlight that physical infrastructure alone does not ensure sustainable service delivery; rather, continuous post-construction support, transparent governance, and adequate financing mechanisms are critical. The study concludes with policy-relevant recommendations aimed at strengthening community management, enhancing post-construction support, and improving the long-term sustainability of rural water supply services in Nepal.